Enhanced earthing performance by improved design and grounding material properties - Mohd Hasni, Nur Alyaa (2018)
An enhance ground electrode (E.G.E.) is a portable grounding system that acts as an additional grounding system, designed for zero potential reference points. The E.G.E could eliminate the increasing of resistance in grounding conductor as it placed next to the electrical equipment, hence the grounding conductor is shortened. A prototype of E.G.E was developed in size measuring 19.5 em x 19.5 em x 11.5 em and filled with selected grounding material, attached with a grounding electrode. Meanwhile, the grounding electrode was reviewed in terms of thermal conductivity electrode material, variation of soil resistivity with the electrode's depth, and effect on the number of grounding rods to ground resistance. The design ofthe electrode was selected based on heat dispersion that was simulated using the Finite Element Method (FEM) package. The four selected grounding materials chosen based on its resistivity value and physical composition which is; kaolin, sand, bauxite and coal. These materials were investigated using the morphology test, element composition test and correlation between water content and material resistivity test. Fabricated E.G.E was tested under lightning flashover conditions in a HV laboratory using an impulse test generator in order to validate its electrical performance and prolog life expectancy. Data obtained from laboratory tests indicated that bauxite is the best material for the proposed E.G.E system, compared to other materials by offering the lowest different percentage breakdown voltage comparable to native earth, which is around 1.27%. Besides that, bauxite gets 35% strikes during dry condition and 38% strikes during wet condition among three others material. It is hope this E.G.E sustaining a good performance as a grounding system.